"Mun mielest nykyään tanssijoiltakin vaaditaan monipuolisempaa otetta kuin aikasemmin" – Nykytanssijan toimijuus muuttuvalla tanssikentällä - Lamberg, Veera (Kulttuuripolitiikan tutkimuksen vuosikirja, 2017)
The agency of the dancer in the changing contemporary dance field in Finland The article discusses the changing professional identity of a contemporary dancer in Finland. The research question is what kind of agency dancers perform in their profession at the moment; Can they be considered as independent auteur artists instead of an instrument of a choreographer? The article is based on the interview study of four freelance dancers. The theoretical framework is the sociological concept of agency, the notion of changing work culture in the postmodern world and the view of social construction of meanings about the dance eld. The data is analysed and organised by themes: the three themes found are a dancer with own artistic voice, an enterprising multitalent, and a responsible negotiator. A dancer with her own artistic voice represents the dancers’ agency towards their own artistic identity, and an enterprising multitalent describes the agency towards the dance eld. A responsible negotiator represents the dancers’ agency towards a dance piece. The conclusion is that the agency of the dancers is expanding and increasing: dancers work more like a creative and independent auteur artist than before.